Testamentum tempore pestis Civil law and bioethics faced with the testament in cases of epidemics - Varsi Rospigliosi, Enrique (Acta Bioethica, 2022)
The confinement due to the Covid pandemic affected the granting of wills, which are so necessary in the health crisis when people need to decide the fate of their property and other individual acts at the risk of life. The solemnity of the will impedes the exercise of testamentary rights of patients, even healthy people. Facilitating the right to testament in times of plague has a bioethical content since life, health, self-determination and the right to decide the destiny of property are at stake. The will in times of pandemic, supported by ICTs, is a solution that should be made feasible with the help of digitization and technology in order to allow the exercise of the rights of last will in isolation by contagion.